Pengaruh Metode Jarimatika Pada Mata Pelajaran Matematika Materi Perkalian Di MI/SD : Studi Meta Analisis - Arifin, Fatkhul; Marliyani, Marliyani (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
This Study aims to analyze the effectiveness of the effect of the Jarimatika method on mathematics multiplication subjects. The research method used is descriptive analysis of the results of scientific research publications in national journals published in the period 2015-202 at the elementary school level which discusses the writing of experiments using the Jarimatika method in mathematics multiplication material. The writing intrument is a coding sheet that summarizes journal data and information. The research findings reveal the overall the studies conducted are influential and effective as a whole with an overall effect size 0.90 which falss into the very large effect category. The Jarimatika method also has an effective effect as seen from the increase in multiplication counting skills, multiplication learning outcomes, motivation to learn to count multiplication, and learning achievement to count multiplication. The conclusion of this study is the Jarimatika method is more effective in mathematics multiplication than the conventional learning model in this study.